2016
DOI: 10.1002/mabi.201600020
|View full text |Cite
|
Sign up to set email alerts
|

Microspheres Assembled from Chitosan‐Graft‐Poly(lactic acid) Micelle‐Like Core–Shell Nanospheres for Distinctly Controlled Release of Hydrophobic and Hydrophilic Biomolecules

Abstract: To simultaneously control inflammation and facilitate dentin regeneration, a copolymeric micelle-in-microsphere platform is developed in this study, aiming to simultaneously release a hydrophobic drug to suppress inflammation and a hydrophilic biomolecule to enhance odontogenic differentiation of dental pulp stem cells in a distinctly controlled fashion. A series of chitosan-graft-poly(lactic acid) (CS-g-PLA) copolymers is synthesized with varying lactic acid (LA) and chitosan (CS) weight ratios (LA/CS), self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…For example, chitosan oligomers (COS), which were hydrolyzed from chitosan, were characterized and found to be a good antibacterial material . To address limitations for its use as an antibacterial material, chemical modifications were made to COS, such as quaternized chitosan oligomers (QCOS) and so on . A recent study found that QCOS had antimicrobial and antioxidant properties in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…For example, chitosan oligomers (COS), which were hydrolyzed from chitosan, were characterized and found to be a good antibacterial material . To address limitations for its use as an antibacterial material, chemical modifications were made to COS, such as quaternized chitosan oligomers (QCOS) and so on . A recent study found that QCOS had antimicrobial and antioxidant properties in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Allograft could be a better substitute, however, lack of osteogenesis and immunological rejection limited its clinical application. Artificial materials are becoming more attractive and popular in studies for bone graft applications . Various biomimetic tissue engineering approaches in terms of artificial materials have been developed to replace autograft and allograft .…”
Section: Introductionmentioning
confidence: 99%
“…Artificial materials are becoming more attractive and popular in studies for bone graft applications. 14,15 Various biomimetic tissue engineering approaches in terms of artificial materials have been developed to replace autograft and allograft. 16 The ideal artificial materials in bone tissue engineering need not only biocompatibility, biodegradation and osteoconduction, but also osteoinduction or favorable delivery system for the osteogenic factor.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study elegantly described a strategy to allow dual drug delivery. 77 A microsphere platform was used to concurrently release fluocinolone acetonide (FA) to suppress inflammation and bone morphogenetic protein 2 (BMP-2) to enhance odontogenic differentiation of DPSCs. A constant linear release of FA, and a rapid BMP-2 release was observed in in vitro systems that reduced inflammation on DPSCs and enhanced differentiation.…”
Section: Advanced Biomaterials For Dental Pulp Regenerationmentioning
confidence: 99%
“…A constant linear release of FA, and a rapid BMP-2 release was observed in in vitro systems that reduced inflammation on DPSCs and enhanced differentiation. 77 …”
Section: Advanced Biomaterials For Dental Pulp Regenerationmentioning
confidence: 99%